Modified Low Complexity Precoding Algorithm for Millimeter Wave MIMO Systems - Rohatgi, Archit; Rawat, Meenakshi (2018 Second International Conference on Intelligent Computing and Control Systems (ICICCS), 2018)
In contrast to conventional multiple-input multiple-output (MIMO) systems, precoding in millimeter wave (mmWave) MIMO systems at baseband is subject to a non-trivial practical constraint which include the number of signal mixers and analog-to-digital converters. Therefore, as a cost-effective alternative, hybrid precoding which comprises of digital and analog precoder has received considerable attention. However, the optimal design of such hybrid structure has not been fully understood. A low complexity algorithm used in practical structures is investigated and a modified version of the algorithm using least squares method is proposed. The results of the proposed algorithm will show the reduction in complexity and improvement in the performance of low complexity alternating minimization algorithm.